Perbaikan Kualitas Tanah Purna Tambang Nikel dengan Penggunaan Mikoriza dan Biochar Tandan Kosong Kelapa Sawit - Titah Kasih Angelita; Burhanuddin Rasyid; Risma Neswati (Universitas Hasanuddin, 2020)
Nickel mining decreases the quality of soil properties, it is not suitable for agriculture so alternative technology is required such us using biochar made from oil palm empty fruit bunch and mycorrhiza. This study aims to examine the effect of biochar made from oil palm empty fruit bunch and mycorrhiza to improve the nickel post-mining soil quality. This study used two-factor factorial randomized group design. The first factor is biochar made from oil palm empty fruit bunch with 4 levels; B0 (0 g), B1 (300 g), B2 (450 g), and B3 (600 g), the second factor is mycorrhiza with 4 levels; M0 (0 g), M1 (2 g), M2 (4 g), each treatment was repeated 3 treatments so that the total experiment was 36 units. The results showed that the use of bio-ameliorant waste from oil palm empty fruit bunch with dosage of 120 g / kg, improved the chemical properties of nickel post-mining soil regarding the parameter of C-organic, pH, available phosphorus, cation exchange capacity, exchangeable aluminum, Ca-dd and Mg -dd and increasing plant growth significantly. The treatment of mycorrhiza 0.4 g / kg significantly affected the soil properties regarding the parameters of root volume, root length and percentage of root infection and improvement of soil chemical properties in available phosphorus to plants and exchangeable aluminum parameters. The treatment of biochar with dosage of 120g / kg of soil and mycorrhiza 0.4 g / kg of soil is the best interaction of mycorrhiza and biochar made from oil palm empty fruit bunch as amelioration material of post-mining soil which is characterized by the decrease of exchangeable aluminum value. The application of biochar made from oil palm empty fruit bunch and mycorrhiza can improve the nickel post-mining soil quality